Characterization of VSV-GP morphology by cryo-EM imaging and SEC-MALS - Dongyue Xin; Leela Kurien; Katherine Briggs; Adrian Schimek; Richard Dambra; Daniel Hochdorfer; Tanja A. Arnouk; Marija Brgles; Saurabh Gautam; Dominik Hotter; Johannes Solzin; Thomas Kriehuber; et al. (Molecular Therapy: Methods & Clinical Development)
Vesicular stomatitis virus expressing the glycoprotein of the lymphocytic choriomeningitis virus (VSV-GP) is a promising platform for oncolytic viruses and cancer vaccines. In this work, cryoelectron microscopy (cryo-EM) imaging was employed to directly visualize VSV-GP particles. Several different subpopulations of virus particle morphology were observed. Definition and fraction counting of subpopulations enabled quantitative comparison of subpopulation profiles between several VSV-GP samples. In developing an orthogonal method with higher throughput, we showed that the morphological profile of the VSV-GP particles can be characterized by size exclusion chromatography coupled with a multi-angle light scattering detector (SEC-MALS) based on a novel shape-based separation mechanism. Together, the two complementary techniques enable the analysis of morphological profile for VSV-GP and potentially other non-spherical viruses or nanoparticles.